Method of hidden transmission of information based on fractals and its software - Gasimov, Vagif A. (Вестник Томского государственного университета. Управление, вычислительная техника и информатика)
In this article is considered hiding process of bits on least significant bits that make up the binary codes of confidential information with using fractal based stego-key. In order to increase resistance against stegoanalysis, it is proposed to use only a part of graphic images not all the pixels of the containers, but only a part determined by the appropriate rule. As a key-image file displaying a Mandelbrot and Julian fractal is used to determine positions of pixels for hiding secret information on least significant pixels of container. So after creation of fractal image as key file, border point of it is changed with according represented rule, then position of pixels is determined with obtained new positions to hiding information in least significant bits.